PELATIHAN BAHASA INGGRIS DAN JEPANG BAGI SIWA AKOMODASI PERHOTELAN DI SMK WIDYA DHARMA BULELENG - Wayan Nurita; Ida Ayu Putri Gita Ardiantari; Ida Bagus Gde Nova Winarta; Ladycia Sundayra (LOKATARA SARASWATI, 2024)
English and Japanese Language Training for students of the Hotel Accommodation expertise program at SMK Widya Dharma Buleleng is carried out as an effort to improve communication competency in foreign languages, especially in the field of tourism. This training program aims to help students acquire basic language skills needed to provide professional services to international tourists and deepen students' knowledge of tourism. The training takes place from February 2024 to June 2024. The training uses an interactive learning approach that emphasizes practical and communication aspects. After the training, students stated that they were able to communicate in English and Japanese in providing hotel services including check-in services, room facility services, check-out services and handling complaints. The results of this training are expected to be able to improve the quality of local tourism services through students' readiness to welcome foreign guests, as well as provide competitive added value in the tourism industry.